High-refraction high-dispersion optical glass
By optimizing the component ratios of SiO2, B2O3, La2O3, Y2O3, ZrO2, Nb2O5, and TiO2, a high refractive high-dispersion optical glass with a refractive index of 1.92 to 1.98 and Abbe number 29 to 36 was designed, which solved the problem of optical glass in harsh environments The problems of short service life and insufficient processing performance achieve excellent weather resistance and wear.
Patent Information
- Application Number
- CN202411334937.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing optical glass has a short service life in harsh environments and lacks processing performance, making it difficult to meet the needs of high refractive index and miniaturized optical instruments.
The combination of SiO2+B2O3: 8-28%, La2O3+Y2O3+Gd2O3: 46-70%, ZrO2: 1-12%, Nb2O5: 4-20%, and TiO2: 4-18% were used to adjust the proportion of each component to obtain The refractive index is 1.92~1.98 and the Abbe number is 29~36, and the wear and weather resistance is improved by optimizing the component design.
It realizes that optical glass has excellent weather resistance and wear at the same time with high refractive index and dispersion, extends its service life, and is suitable for high-fine optical instruments and harsh environments.
Smart Images

Figure BDA0005058006130000121 
Figure BDA0005058006130000132 
Figure BDA0005058006130000151
Abstract
Description
[0001] This application is a divisional application for the invention patent application with application number 202211031612.8, application date August 26, 2022, and name “High refractive and high dispersion optical glass”. Technical Field
[0002] The invention relates to an optical glass, in particular to a high-refractive and high-dispersion optical glass with excellent weather resistance and abrasion resistance. Background Art
[0003] In recent years, the rapid development of digitalization and high precision of optical instruments has put forward higher requirements for the lightweight and miniaturization of optical components used in various optical instruments such as digital cameras, video cameras and other photographic equipment, projectors, projection televisions and other projection equipment. Under the same radius of curvature, the higher the refractive index of the glass, the larger the imaging field of view, which is conducive to reducing the number of optical components in the optical instrument. With the development trend of miniaturization of optical instruments, the demand for high refractive index glass is becoming more and more obvious. At the same time, with the rapid development of monitoring security, vehicle-mounted imaging and other fields, high refractive index optical glass is also widely used in monitoring, vehicle-mounted and other fields, and the optical glass used in the above fields is required to have excellent weather resistance to extend the service life of the optical glass in harsh environments.
[0004] In the process of optical component processing, glass preforms can be made by mechanical processing such as grinding and polishing of optical glass, or by making a preform for molding from optical glass, hot-pressing the preform and then grinding it to make a glass preform, or by precision stamping the preform made by grinding to make a glass preform. This requires that the optical glass has good processing performance and excellent abrasion resistance. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a high-refractive and high-dispersion optical glass with excellent weather resistance and abrasion resistance.
[0006] The technical solution adopted by the present invention to solve the technical problem is:
[0007] (1) High refractive and high dispersion optical glass, the components of which are expressed in weight percentage and contain: SiO 2 +B 2 O 3 : 8~28%; La 2 O 3 +Y 2 O 3 +Gd 2 O 3 :46~70%;ZrO 2 :1~12%;Nb2 O 5 :4~20%;TiO 2 : 4~18%, of which TiO 2 / Y 2 O 3 It is 0.3~4.0.
[0008] (2) The high-refractive and high-dispersion optical glass according to (1), wherein the components thereof, expressed in weight percentage, further contain: Ta 2 O 5 : 0~8%; and / or RO: 0~9%; and / or Rn 2 O: 0~6%; and / or WO 3 : 0-6%; and / or ZnO: 0-8%; and / or Al 2 O 3 :0~5%;and / or Yb 2 O 3 :0~10%;and / or GeO 2 : 0-5%; and / or clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO, BaO, Rn 2 O is Li 2 O、Na 2 O.K 2 O, the clarifier is Sb 2 O 3 、SnO、SnO 2 、CeO 2 One or more of .
[0009] (3) High refractive and high dispersion optical glass containing ZrO 2 , Nb 2 O 5 、TiO 2 , its composition is expressed in weight percentage, containing 8 to 28% SiO 2 +B 2 O 3 and 46-70% La 2 O 3 +Y 2 O 3 +Gd 2 O 3 , where TiO 2 / Y 2 O 3 The refractive index n of the high-refractive and high-dispersion optical glass is 0.3 to 4.0. d is 1.92~1.98, Abbe number v d 29~36, wear degree F AThe temperature is 80 to 130, and the weather resistance CR is 2 or above.
[0010] (4) The high-refractive and high-dispersion optical glass according to (3), wherein the composition, expressed in weight percentage, comprises: ZrO 2 :1~12%;and / or Nb 2 O 5 : 4-20%; and / or TiO 2 : 4-18%; and / or Ta 2 O 5 : 0~8%; and / or RO: 0~9%; and / or Rn 2 O: 0~6%; and / or WO 3 : 0-6%; and / or ZnO: 0-8%; and / or Al 2 O 3 :0~5%;and / or Yb 2 O 3 :0~10%;and / or GeO 2 : 0-5%; and / or clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO, BaO, Rn 2 O is Li 2 O、Na 2 O.K 2 O, the clarifier is Sb 2 O 3 、SnO、SnO 2 、CeO 2 One or more of .
[0011] (5) The high-refractive and high-dispersion optical glass according to any one of (1) to (4), wherein the components thereof, expressed in weight percentage, satisfy one or more of the following nine conditions:
[0012] 1) La 2 O 3 / (TiO 2 +Nb 2 O 5 ) is 1.2 to 6.0, preferably La 2 O 3 / (TiO 2 +Nb 2 O 5 ) is 1.5 to 5.0, and more preferably La 2 O 3 / (TiO 2 +Nb 2 O 5 ) is 2.0 to 4.0, and La 2 O 3 / (TiO 2+Nb 2 O 5 ) is 2.5 to 3.5;
[0013] 2) TiO 2 / Y 2 O 3 0.5 to 3.0, preferably TiO 2 / Y 2 O 3 0.6 to 2.0, more preferably TiO 2 / Y 2 O 3 0.75~1.5;
[0014] 3) Y 2 O 3 / B 2 O 3 0.4 to 3.0, preferably Y 2 O 3 / B 2 O 3 0.5 to 2.5, more preferably Y 2 O 3 / B 2 O 3 is 0.6 to 1.5, and Y 2 O 3 / B 2 O 3 0.7~1.2;
[0015] 4)(B 2 O 3 +TiO 2 ) / (SiO 2 + ZnO) is 1.0 to 10.0, preferably (B 2 O 3 +TiO 2 ) / (SiO 2 + ZnO) is 1.0 to 8.0, and more preferably (B 2 O 3 +TiO 2 ) / (SiO 2 + ZnO) is 1.5 to 7.0, and more preferably (B 2 O 3 +TiO 2 ) / (SiO 2 + ZnO) is 2.0 to 5.0;
[0016] 5)(Ta 2 O 5 +Gd 2 O 3 ) / Y 2 O3 is 1.0 or less, preferably (Ta 2 O 5 +Gd 2 O 3 ) / Y 2 O 3 is 0.6 or less, more preferably (Ta 2 O 5 +Gd 2 O 3 ) / Y 2 O 3 is 0.4 or less, and more preferably (Ta 2 O 5 +Gd 2 O 3 ) / Y 2 O 3 is less than 0.1;
[0017] 6) TiO 2 / (Nb 2 O 5 +WO 3 ) is 0.3 to 3.0, preferably TiO 2 / (Nb 2 O 5 +WO 3 ) is 0.4 to 2.0, and more preferably TiO 2 / (Nb 2 O 5 +WO 3 ) is 0.6 to 1.5, and TiO 2 / (Nb 2 O 5 +WO 3 ) is 0.8~1.3;
[0018] 7) ZnO / (SiO 2 +B 2 O 3 ) is 0.5 or less, preferably ZnO / (SiO 2 +B 2 O 3 ) is 0.3 or less, and more preferably ZnO / (SiO 2 +B 2 O 3 ) is 0.2 or less, and ZnO / (SiO 2 +B 2 O 3 ) is less than 0.1;
[0019] 8)(Gd 2 O 3 +ZnO) / Y 2 O3 is 1.0 or less, preferably (Gd 2 O 3 +ZnO) / Y 2 O 3 is 0.6 or less, more preferably (Gd 2 O 3 +ZnO) / Y 2 O 3 is 0.3 or less, and more preferably (Gd 2 O 3 +ZnO) / Y 2 O 3 is less than 0.1;
[0020] 9)WO 3 / Y 2 O 3 0.8 or less, preferably WO 3 / Y 2 O 3 0.6 or less, more preferably WO 3 / Y 2 O 3 0.02 to 0.5, more preferably WO 3 / Y 2 O 3 It is 0.05~0.3.
[0021] (6) The high-refractive and high-dispersion optical glass according to any one of (1) to (4), wherein the components are expressed in weight percentage, wherein: La 2 O 3 +Y 2 O 3 +Gd 2 O 3 : 50-68%, preferably La 2 O 3 +Y 2 O 3 +Gd 2 O 3 :55~65%;and / or SiO 2 +B 2 O 3 : 10-25%, preferably SiO 2 +B 2 O 3 :12~20%;and / or ZrO 2 : 3-10%, preferably ZrO 2 : 4-9%; and / or Nb 2 O 5 : 5-15%, preferably Nb 2 O 5 : 7-12%; and / or Ta2 O 5 : 0~4%, preferably Ta 2 O 5 :0~2%;and / or TiO 2 : 5-13%, preferably TiO 2 : 6-12%; and / or RO: 0-4%, preferably RO: 0-2%; and / or Rn 2 O: 0-4%, preferably Rn 2 O: 0~1%; and / or WO 3 : 0-4%, preferably WO 3 : 0.5-3%; and / or ZnO: 0-4%, preferably ZnO: 0-2%; and / or Al 2 O 3 : 0-3%, preferably Al 2 O 3 :0~1%;and / or Yb 2 O 3 : 0-5%, preferably Yb 2 O 3 :0~1%;and / or GeO 2 : 0-3%, preferably GeO 2 : 0-1%; and / or clarifier: 0-1%, preferably clarifier: 0-0.5%, wherein RO is one or more of MgO, CaO, SrO, BaO, Rn 2 O is Li 2 O、Na 2 O.K 2 O, the clarifier is Sb 2 O 3 、SnO、SnO 2 、CeO 2 One or more of .
[0022] (7) The high-refractive and high-dispersion optical glass according to any one of (1) to (4), wherein the components are expressed in weight percentage, wherein: SiO 2 : 1-12%, preferably SiO 2 : 2 to 10%, more preferably SiO 2 : 4-9%; and / or B 2 O 3 : 5-18%, preferably B 2 O 3 : 6-14%, more preferably B 2 O 3 : 7-12%; and / or La 2 O 3 : 40-60%, preferably La 2 O 3: 43-58%, more preferably La 2 O 3 : 46-53%; and / or Y 2 O 3 : 4-20%, preferably Y 2 O 3 : 5-15%, more preferably Y 2 O 3 : 6-12%; and / or Gd 2 O 3 : 0-9%, preferably Gd 2 O 3 : 0-5%, more preferably Gd 2 O 3 : 0 to 3%, more preferably Gd 2 O 3 :0~1%.
[0023] (8) The high-refractive and high-dispersion optical glass according to any one of (1) to (4), wherein the components thereof are expressed in weight percentage: SiO 2 , B 2 O 3 ,La 2 O 3 , Y 2 O 3 、ZrO 2 , Nb 2 O 5 、TiO 2 The total content of SiO is 88% or more, preferably SiO 2 , B 2 O 3 ,La 2 O 3 , Y 2 O 3 、ZrO 2 , Nb 2 O 5 、TiO 2 The total content of SiO is 90% or more, preferably SiO 2 , B 2 O 3 ,La 2 O 3 , Y 2 O 3 、ZrO 2 , Nb 2 O 5 、TiO 2 The total content of SiO is 92% or more, and more preferably SiO 2 , B 2 O 3 ,La 2 O3 , Y 2 O 3 、ZrO 2 , Nb 2 O 5 、TiO 2 The total content is 95% or more.
[0024] (9) The high-refractive and high-dispersion optical glass according to any one of (1) to (4), wherein the composition does not contain Ta 2 O 5 ; and / or does not contain Yb 2 O 3 ; and / or does not contain RO; and / or does not contain Rn 2 O; and / or does not contain ZnO; and / or does not contain Al 2 O 3 ; and / or does not contain GeO 2 , the RO is one or more of MgO, CaO, SrO, BaO, Rn 2 O is Li 2 O、Na 2 O.K 2 One or more of O.
[0025] (10) According to any one of (1) to (4) of the high-refractive and high-dispersion optical glass, the refractive index n of the high-refractive and high-dispersion optical glass is d is 1.92 to 1.98, preferably 1.93 to 1.97, more preferably 1.94 to 1.96, and the Abbe number v d It is 29-36, preferably 30-35, and more preferably 31-34.
[0026] (11) The high-refractive and high-dispersion optical glass according to any one of (1) to (4), wherein the density ρ of the high-refractive and high-dispersion optical glass is 5.10 g / cm 3 Below, preferably 5.00 g / cm 3 Below, more preferably 4.95g / cm 3 Below; and / or thermal expansion coefficient α -30 / 70℃ 85×10 -7 / K or less, preferably 80×10 -7 / K or less, more preferably 75×10 -7 / K or less, more preferably 70×10 -7 / K or less; and / or water resistance stability D W 2 or more, preferably 1; and / or acid resistance stability D A Two or more types, preferably one type; and / or 70 425nm or less, preferably λ70 420nm or less, preferably λ 70 is below 415nm; and / or λ 5 375nm or less, preferably λ 5 370nm or less, preferably λ 5 365nm or less; and / or weather resistance CR is 2 or more, preferably 1; and / or Knoop hardness H K 650×10 7 Pa or more, preferably 660×10 7 Pa or more, more preferably 670×10 7 Pa or more, more preferably 680×10 7 Pa or more; and / or Young's modulus E is 11000×10 7 Pa~15000×10 7 Pa, preferably 11500×10 7 Pa~14500×10 7 Pa, more preferably 12000×10 7 Pa~14000×10 7 Pa, more preferably 12500×10 7 Pa~13500×10 7 Pa; and / or the bubble degree is above grade A, preferably A 0 Grade A or above, preferably A 00 Grade; and / or wear degree F A It is 80-130, preferably 90-120, more preferably 95-115.
[0027] (12) A glass preform made of the high-refractive and high-dispersion optical glass described in any one of (1) to (11).
[0028] (13) An optical element is made of the high-refractive and high-dispersion optical glass described in any one of (1) to (11), or is made of the glass preform described in (12).
[0029] (14) An optical instrument comprising the high-refractive and high-dispersion optical glass described in any one of (1) to (11), and / or the optical element described in (13).
[0030] The beneficial effects of the present invention are: through reasonable component design, the optical glass of the present invention has the desired refractive index and dispersion, as well as excellent weather resistance and abrasion resistance. DETAILED DESCRIPTION
[0031] The following is a detailed description of the embodiments of the high-refractive and high-dispersion optical glass of the present invention, but the present invention is not limited to the following embodiments, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, although there are cases where the repeated description is appropriately omitted, the main purpose of the invention is not limited thereto. In the following content, the high-refractive and high-dispersion optical glass of the present invention is sometimes referred to as optical glass or glass.
[0032] [High refractive and high dispersion optical glass]
[0033] The following is an explanation of the range of each component (ingredient) of the high-refractive and high-dispersion optical glass of the present invention. In the present invention, unless otherwise specified, the content and total content of each component are all expressed in weight percentage (wt%), that is, the content and total content of each component are expressed in weight percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when the oxides, complex salts and hydroxides used as raw materials for the optical glass components of the present invention decompose and transform into oxides during melting, the total amount of the oxide material is taken as 100%.
[0034] Unless otherwise specified in specific circumstances, the numerical ranges listed in the present invention include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0035] <Essential Components and Optional Components>
[0036] B 2 O 3 In the present invention, it is a network forming component, which can improve the thermal stability of glass and enhance the melting property of glass. 2 O 3 To obtain the above effect, preferably B 2 O 3 The content of B is 6% or more, preferably 2 O 3 The content of B is 7% or more. 2 O 3 When the content of B is too high, the refractive index of the glass decreases and the chemical stability deteriorates. 2 O 3 The upper limit of the content is 18%, preferably 14%, and more preferably 12%.
[0037] SiO 2It has the effects of improving the chemical stability of glass, maintaining the viscosity suitable for molten glass molding, and reducing the corrosion of refractory materials. If its content is too high, the melting difficulty of glass increases, and it is not conducive to reducing the transition temperature of glass. 2 The content of is 1 to 12%, preferably 2 to 10%, and more preferably 4 to 9%.
[0038] In some embodiments, by placing SiO 2 and B 2 O 3 Total content of SiO 2 +B 2 O 3 Controlling it within the range of 8-28% can optimize the abrasion resistance and weather resistance of the glass while maintaining the stability of the glass, and prevent the glass from losing clarity. 2 +B 2 O 3 8 to 28%, more preferably SiO 2 +B 2 O 3 10 to 25%, more preferably SiO 2 +B 2 O 3 It is 12 to 20%.
[0039] La 2 O 3 It is an effective component for improving the refractive index of glass and has a significant effect on improving the chemical stability and resistance to devitrification of glass. If its content is less than 40%, it is difficult to achieve the required optical constants; if the content is higher than 60%, the devitrification tendency of the glass increases and the thermal stability deteriorates. Therefore, La 2 O 3 The content of is limited to 40 to 60%, preferably 43 to 58%, and more preferably 46 to 53%.
[0040] Y 2 O 3 The refractive index and devitrification resistance of the glass can be improved, and the Young's modulus of the glass can be adjusted. 2 O 3 To obtain the above effects; if its content exceeds 20%, the chemical stability and weather resistance of the glass will deteriorate. 2 O 3 The content is 4 to 20%, preferably 5 to 15%, and more preferably 6 to 12%.
[0041] In some embodiments, Y 2 O 3 The content of B 2 O 3The ratio Y between the contents 2 O 3 / B 2 O 3 Controlling it within the range of 0.4 to 3.0 is beneficial for the glass to obtain an appropriate Young's modulus. 2 O 3 / B 2 O 3 0.4 to 3.0, more preferably Y 2 O 3 / B 2 O 3 is 0.5 to 2.5. Further, by 2 O 3 / B 2 O 3 Controlling it within the range of 0.6 to 1.5 is beneficial to further reduce the thermal expansion coefficient of the glass and optimize the bubble degree of the glass. 2 O 3 / B 2 O 3 is 0.6 to 1.5, and Y is more preferably 2 O 3 / B 2 O 3 It is 0.7~1.2.
[0042] G 2 O 3 It can improve the refractive index and chemical stability of glass, but if its content is too high, the devitrification resistance and abrasion resistance of the glass will deteriorate, and the cost of the glass will increase. 2 O 3 The content of is 0 to 9%, preferably 0 to 5%, more preferably 0 to 3%, and further preferably 0 to 1%.
[0043] In some embodiments, by 2 O 3 , Y 2 O 3 and Gd 2 O 3 Total content La 2 O 3 +Y 2 O 3 +Gd 2 O 3 When La is controlled within the range of 46-70%, the glass can more easily obtain the desired refractive index and Abbe number, and optimize the glass's resistance to devitrification and weather resistance. 2 O 3 +Y 2 O 3 +Gd 2O 3 46 to 70%, more preferably La 2 O 3 +Y 2 O 3 +Gd 2 O 3 50 to 68%, more preferably La 2 O 3 +Y 2 O 3 +Gd 2 O 3 It is 55 to 65%.
[0044] Yb 2 O 3 It is also a component that gives glass high refractive index and low dispersion properties. If its content exceeds 10%, the anti-crystallization performance of the glass will decrease. 2 O 3 The content of Yb is 0 to 10%, preferably 0 to 5%, more preferably 0 to 1%, and more preferably no Yb 2 O 3 .
[0045] ZrO 2 It can improve the viscosity, hardness, refractive index and chemical stability of optical glass, and can also reduce the thermal expansion coefficient of glass; when ZrO 2 When the content of ZrO is too high, the devitrification resistance of the glass decreases, the melting difficulty increases, the melting temperature rises, and inclusions appear inside the glass and the light transmittance decreases. 2 The content of is 1 to 12%, preferably 3 to 10%, and more preferably 4 to 9%.
[0046] TiO 2 It is a high-refractive and high-dispersion component that can significantly increase the refractive index and dispersion of glass. The inventors found that a proper amount of TiO 2 It can increase the stability of glass; however, if it contains too much TiO 2 , the transmittance of the glass will be significantly reduced, and the chemical stability of the glass will also tend to deteriorate. 2 The content of is 4 to 18%, preferably 5 to 13%, and more preferably 6 to 12%.
[0047] In some embodiments, TiO 2 The content of Y 2 O 3 The ratio between the content of TiO 2 / Y 2 O 3Controlling it within the range of 0.3 to 4.0 can optimize the abrasion resistance and weather resistance of the glass. 2 / Y 2 O 3 0.3 to 4.0, more preferably TiO 2 / Y 2 O 3 is 0.5 to 3.0. Further, control TiO 2 / Y 2 O 3 In the range of 0.6 to 2.0, the chemical stability and bubble degree of the glass can be further improved. Therefore, TiO 2 / Y 2 O 3 is 0.6 to 2.0, and TiO is more preferred 2 / Y 2 O 3 It is 0.75~1.5.
[0048] Nb 2 O 5 It is a high refractive and high dispersion component, which can improve the refractive index and devitrification resistance of glass and reduce the thermal expansion coefficient of glass. 2 O 5 In order to obtain the above effects, Nb is preferably 2 O 5 The lower limit of the content of Nb is 5%, and the more preferred lower limit is 7%. 2 O 5 The content of Nb exceeds 20%, the thermal stability and weather resistance of the glass decrease, and the light transmittance decreases. Therefore, in the present invention, 2 O 5 The upper limit of the content is 20%, preferably 15%, and more preferably 12%.
[0049] In some embodiments, La 2 O 3 The content of TiO 2 and Nb 2 O 5 The ratio of the total content of La 2 O 3 / (TiO 2 +Nb 2 O 5 ) is controlled within the range of 1.2 to 6.0, which is beneficial to improving the Young's modulus of the glass and preventing the glass light transmittance from decreasing. 2 O 3 / (TiO 2 +Nb 2 O 5) is 1.2 to 6.0, and more preferably La 2 O 3 / (TiO 2 +Nb 2 O 5 ) is 1.5 to 5.0. Further, control La 2 O 3 / (TiO 2 +Nb 2 O 5 ) in the range of 2.0 to 4.0, the density and thermal expansion coefficient of the glass can be further reduced. 2 O 3 / (TiO 2 +Nb 2 O 5 ) is 2.0 to 4.0, and La 2 O 3 / (TiO 2 +Nb 2 O 5 ) is 2.5~3.5.
[0050] Alkaline earth metal oxide RO (RO is one or more of MgO, CaO, SrO, BaO) can adjust the optical constants of glass and optimize the chemical stability of glass, but when its content is high, the devitrification resistance of glass decreases. Therefore, the RO content is limited to 0-9%, preferably 0-4%, and more preferably 0-2%. In some embodiments, it is further preferred that RO is not contained.
[0051] Alkali metal oxide Rn 2 O(Rn 2 O is Li 2 O、Na 2 O.K 2 O) can reduce the transition temperature of glass, adjust the optical constants and high temperature viscosity of glass, and improve the melting property of glass. However, when its content is high, the devitrification resistance and chemical stability of glass are reduced. 2 The content of O is 0 to 6%, preferably 0 to 4%, and more preferably 0 to 1%. In some embodiments, it is further preferred that Rn 2 O.
[0052] WO 3 It can improve the refractive index and mechanical strength of glass. 3 When the content of WO exceeds 6%, the thermal stability of the glass decreases and the resistance to devitrification decreases. 3 The content of is 0 to 6%, preferably 0 to 4%, and more preferably 0.5 to 3%.
[0053] In some embodiments, WO 3 The content of Y 2 O 3 The ratio between the content of WO 3 / Y 2 O 3 Controlling it below 0.8 is beneficial to improving the chemical stability and anti-devitrification of the glass. 3 / Y 2 O 3 0.8 or less, more preferably WO 3 / Y 2 O 3 is below 0.6. Further, control WO 3 / Y 2 O 3 In the range of 0.02 to 0.5, the hardness and bubble degree of the glass can be further optimized. 3 / Y 2 O 3 0.02 to 0.5, more preferably WO 3 / Y 2 O 3 It is 0.05~0.3.
[0054] In some embodiments, TiO 2 The content of Nb 2 O 5 and WO 3 Total content Nb 2 O 5 +WO 3 The ratio of TiO 2 / (Nb 2 O 5 +WO 3 ) is controlled within the range of 0.3 to 3.0, which can reduce the density of the glass while preventing the light transmittance of the glass from decreasing. Therefore, TiO 2 / (Nb 2 O 5 +WO 3 ) is 0.3 to 3.0, and more preferably TiO 2 / (Nb 2 O 5 +WO 3 ) is 0.4 to 2.0. Further, control TiO 2 / (Nb 2 O 5 +WO 3 ) is within the range of 0.6 to 1.5, the Young's modulus and weather resistance of the glass can be further optimized. Therefore, TiO 2 / (Nb2 O 5 +WO 3 ) is 0.6 to 1.5, and TiO 2 / (Nb 2 O 5 +WO 3 ) is 0.8~1.3.
[0055] ZnO can adjust the refractive index and dispersion of glass, and reduce the high temperature viscosity and transition temperature of glass. If the content of ZnO is too high, the difficulty of glass molding increases and the anti-crystallization performance deteriorates. Therefore, the content of ZnO is 0 to 8%, preferably 0 to 4%, and more preferably 0 to 2%. In some embodiments, it is further preferred that ZnO is not contained.
[0056] In some embodiments, the content of ZnO and SiO 2 and B 2 O 3 Total content of SiO 2 +B 2 O 3 The ratio between ZnO / (SiO 2 +B 2 O 3 ) is controlled below 0.5, which can improve the melting property of glass, increase the bubble degree and optimize the abrasiveness. Therefore, ZnO / (SiO 2 +B 2 O 3 ) is 0.5 or less, and more preferably ZnO / (SiO 2 +B 2 O 3 ) is 0.3 or less, and ZnO / (SiO 2 +B 2 O 3 ) is 0.2 or less, and ZnO / (SiO 2 +B 2 O 3 ) is less than 0.1.
[0057] In some embodiments, B 2 O 3 and TiO 2 Total content B 2 O 3 +TiO 2 With SiO 2 The total content of SiO and ZnO 2 + ZnO ratio (B 2 O 3 +TiO 2 ) / (SiO 2+ ZnO) is controlled within the range of 1.0 to 10.0, which can improve the chemical stability of the glass and prevent the glass light transmittance from decreasing. 2 O 3 +TiO 2 ) / (SiO 2 + ZnO) is 1.0 to 10.0, and more preferably (B 2 O 3 +TiO 2 ) / (SiO 2 + ZnO) is 1.0 to 8.0. Further, by controlling (B 2 O 3 +TiO 2 ) / (SiO 2 + ZnO) in the range of 1.5 to 7.0 can further increase the hardness of the glass and reduce the thermal expansion coefficient of the glass. 2 O 3 +TiO 2 ) / (SiO 2 + ZnO) is 1.5 to 7.0, and more preferably (B 2 O 3 +TiO 2 ) / (SiO 2 +ZnO) is 2.0~5.0.
[0058] In some embodiments, by adding Gd 2 O 3 The total content of Gd and ZnO 2 O 3 +ZnO and Y 2 O 3 The ratio between the contents of Gd 2 O 3 +ZnO) / Y 2 O 3 Controlling below 1.0 can reduce the thermal expansion coefficient of the glass and optimize the abrasiveness of the glass. 2 O 3 +ZnO) / Y 2 O 3 is 1.0 or less, more preferably (Gd 2 O 3 +ZnO) / Y 2 O 3 is less than 0.6. Further, control (Gd 2 O 3 +ZnO) / Y 2 O 3When the value is below 0.3, the glass can more easily obtain a suitable Young's modulus and prevent the glass hardness from decreasing. 2 O 3 +ZnO) / Y 2 O 3 is 0.3 or less, and more preferably (Gd 2 O 3 +ZnO) / Y 2 O 3 Is less than 0.1.
[0059] Ta 2 O 5 It has the effect of increasing the refractive index and improving the devitrification resistance of glass. However, if its content is too high, the thermal stability of the glass will decrease and the density will increase. On the other hand, compared with other components, Ta 2 O 5 The price of Ta is very expensive, and from the perspective of practicality and cost, its usage should be reduced as much as possible. 2 O 5 The content of Ta is limited to 0-8%, preferably 0-4%, and more preferably 0-2%. In some embodiments, it is further preferred that Ta is not contained. 2 O 5 .
[0060] In some embodiments, Ta 2 O 5 and Gd 2 O 3 Total content Ta 2 O 5 +Gd 2 O 3 With Y 2 O 3 The ratio between the contents of 2 O 5 +Gd 2 O 3 ) / Y 2 O 3 Controlling it below 1.0 is beneficial for the glass to obtain a suitable abrasiveness, optimize the density and Young's modulus of the glass, and prevent the chemical stability of the glass from deteriorating. 2 O 5 +Gd 2 O 3 ) / Y 2 O 3 is 1.0 or less, more preferably (Ta 2 O 5 +Gd 2 O 3 ) / Y 2 O 3is 0.6 or less, and more preferably (Ta 2 O 5 +Gd 2 O 3 ) / Y 2 O 3 is 0.4 or less, and more preferably (Ta 2 O 5 +Gd 2 O 3 ) / Y 2 O 3 Is less than 0.1.
[0061] Al 2 O 3 It can improve the chemical stability of glass, but when its content exceeds 5%, the melting property and light transmittance of glass deteriorate. 2 O 3 The content of Al is 0-5%, preferably 0-3%, and more preferably 0-1%. In some embodiments, it is further preferred that Al is not contained. 2 O 3 .
[0062] GeO 2 It has the effect of increasing the refractive index and resistance to devitrification, but if its content is too high, the chemical stability of the glass will decrease. On the other hand, compared with other components, GeO 2 The price of GeO is very expensive, and from the perspective of practicality and cost, its usage should be reduced as much as possible. 2 The content of GeO is limited to 0-5%, preferably 0-3%, more preferably 0-1%, and more preferably no GeO 2 .
[0063] In the present invention, 0 to 2% of Sb is contained 2 O 3 、SnO、SnO 2 、CeO 2 One or more components in the glass can be used as a clarifier to improve the clarification effect of the glass and the bubble degree of the glass. The content of the clarifier is preferably 0-1%, and more preferably 0-0.5%. Since the component types and contents of the optical glass of the present invention are reasonably designed and the bubble degree is excellent, it is further preferred in some embodiments that no clarifier is contained. When Sb 2 O 3 When the content exceeds 2%, the glass tends to have a reduced clarity performance. At the same time, due to its strong oxidizing effect, it promotes the corrosion of platinum or platinum alloy vessels for melting glass and the deterioration of the molding mold. Therefore, Sb is preferably used in the present invention. 2 O 3The content of Sb is 0 to 2%, more preferably 0 to 1%, further preferably 0 to 0.5%, and further preferably no Sb 2 O 3 . SnO and SnO 2 It can also be used as a clarifier, but when its content exceeds 2%, the glass tends to be colored more, or when the glass is heated, softened, and molded again, Sn will become the starting point for the formation of crystal nuclei, resulting in a tendency to devitrification. 2 The content of SnO is preferably 0 to 2%, more preferably 0 to 1%, further preferably 0 to 0.5%, and further preferably does not contain SnO 2 The content of SnO is preferably 0 to 2%, more preferably 0 to 1%, further preferably 0 to 0.5%, and further preferably contains no SnO. CeO 2 The role and content ratio of SnO 2 The content is preferably 0 to 2%, more preferably 0 to 1%, further preferably 0 to 0.5%, and further preferably CeO is not contained. 2 .
[0064] In some embodiments, in order to obtain a lower thermal expansion coefficient and density, a higher light transmittance and bubble level, and a suitable abrasion resistance and Young's modulus for the high-refractive and high-dispersion optical glass of the present invention, SiO 2 , B 2 O 3 ,La 2 O 3 , Y 2 O 3 、ZrO 2 , Nb 2 O 5 、TiO 2 The total content of SiO is 88% or more, preferably SiO 2 , B 2 O 3 ,La 2 O 3 , Y 2 O 3 、ZrO 2 , Nb 2 O 5 、TiO 2 The total content of SiO is 90% or more, and SiO 2 , B 2 O 3 ,La 2 O 3 , Y 2 O 3 、ZrO 2 , Nb 2 O5 、TiO 2 The total content of SiO is 92% or more, and more preferably SiO 2 , B 2 O 3 ,La 2 O 3 , Y 2 O 3 、ZrO 2 , Nb 2 O 5 、TiO 2 The total content is 95% or more.
[0065] <Components that should not be contained>
[0066] In the glass of the present invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo are contained alone or in combination in small amounts, the glass will be colored and absorption will occur at specific wavelengths in the visible light region, thereby weakening the property of the present invention of improving the visible light transmittance. Therefore, it is preferably substantially free of oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, especially for optical glasses that require transmittance at wavelengths in the visible light region.
[0067] The oxides of Th, Cd, Tl, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are not actually contained except for being inevitably mixed in. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can be manufactured, processed and discarded.
[0068] In order to achieve environmental friendliness, the high-refractive and high-dispersion optical glass of the present invention preferably does not contain As. 2 O 3 and PbO.
[0069] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the high-refractive and high-dispersion optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be certain impurities or components that are not intentionally added, which will be contained in small amounts or trace amounts in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.
[0070] Next, the properties of the high-refractive and high-dispersion optical glass of the present invention will be described.
[0071] <Refractive Index and Abbe Number>
[0072] The refractive index of optical glass (n d ) and the Abbe number (ν d ) Tested according to the method specified in GB / T 7962.1-2010.
[0073] In some embodiments, the refractive index (n d ) has a lower limit of 1.92, a preferred lower limit of 1.93, and a more preferred lower limit of 1.94.
[0074] In some embodiments, the refractive index (n d ) is 1.98, preferably 1.97, and more preferably 1.96.
[0075] In some embodiments, the Abbe number (ν d ) has a lower limit of 29, a preferred lower limit of 30, and a more preferred lower limit of 31.
[0076] In some embodiments, the Abbe number (ν d ) has an upper limit of 36, a preferred upper limit of 35, and a more preferred upper limit of 34.
[0077] <density>
[0078] The density (ρ) of optical glass is tested according to the method specified in GB / T7962.20-2010.
[0079] In some embodiments, the density (ρ) of the high refractive and high dispersion optical glass of the present invention is 5.10 g / cm 3 Below, preferably 5.00 g / cm 3 Below, more preferably 4.95g / cm 3 the following.
[0080] <Coefficient of Thermal Expansion>
[0081] Thermal expansion coefficient of optical glass (α -30 / 70℃ ) The data at -30~70℃ were tested according to the method specified in GB / T7962.16-2010.
[0082] In some embodiments, the thermal expansion coefficient (α -30 / 70℃ ) is 85×10 -7 / K or less, preferably 80×10 -7 / K or less, more preferably 75×10 -7 / K or less, more preferably 70×10 -7 / K or less.
[0083] <Water resistance stability>
[0084] Water resistance stability of optical glass (D W ) (Powder method) Tested in accordance with the method specified in GB / T 17129.
[0085] In some embodiments, the water resistance stability (D W ) is 2 or more types, preferably 1 type.
[0086] <Acid resistance stability>
[0087] Acid resistance stability of optical glass (D A ) (Powder method) Tested in accordance with the method specified in GB / T 17129.
[0088] In some embodiments, the acid resistance stability (D A ) is 2 or more types, preferably 1 type.
[0089] <Color>
[0090] The short-wave transmission spectrum characteristics of the glass of the present invention are expressed by the coloration (λ 70 and λ 5 ) indicates. 70 Refers to the wavelength when the glass transmittance reaches 70%. 70 The measurement is to use a glass with a thickness of 10±0.1mm and two opposite planes parallel to each other and optically polished, and measure the spectral transmittance in the wavelength range from 280nm to 700nm and the wavelength at which the transmittance is 70%. The so-called spectral transmittance or transmittance is the wavelength at which the incident intensity I is perpendicular to the above surface of the glass. in Light of intensity I passes through the glass and emerges from a plane out The light of the case through I out / I in The amount expressed by λ also includes the transmittance of the surface reflection loss on the above surfaces of the glass. The higher the refractive index of the glass, the greater the surface reflection loss. Therefore, in high refractive index glass, λ 70 A small value of means that the glass itself is less colored and has a high light transmittance.
[0091] In some embodiments, the λ of the high refractive and high dispersion optical glass of the present invention is 70 425nm or less, preferably λ 70 420nm or less, preferably λ 70 Below 415nm.
[0092] In some embodiments, the λ of the high refractive and high dispersion optical glass of the present invention is5 375nm or less, preferably λ 5 370nm or less, preferably λ 5 Below 365nm.
[0093] <Weather resistance>
[0094] The test method for weather resistance (CR) of optical glass is as follows: place the sample in a test box with a saturated water vapor environment of 90% relative humidity, alternately cycle every 1 hour at 40-50°C, and cycle for 15 cycles. The weather resistance category is divided according to the change in turbidity before and after the sample is placed. The weather resistance classification is shown in Table 1:
[0095] Table 1.
[0096]
[0097]
[0098] In some embodiments, the weather resistance (CR) of the high-refractive and high-dispersion optical glass of the present invention is Class 2 or higher, preferably Class 1.
[0099] <Knoop hardness>
[0100] Knoop hardness of optical glass (H K ) The test shall be carried out according to the test method specified in GB / T7962.18-2010.
[0101] In some embodiments, the Knoop hardness (H K ) is 650×10 7 Pa or more, preferably 660×10 7 Pa or more, more preferably 670×10 7 Pa or more, more preferably 680×10 7 Pa or above.
[0102] <Young's modulus>
[0103] Young's modulus (E) is calculated using the following formula by ultrasonic testing of its longitudinal wave velocity and transverse wave velocity.
[0104]
[0105] G=V S 2 ρ
[0106] Where: E is Young's modulus, Pa;
[0107] G is the shear modulus, Pa;
[0108] VT is the shear wave velocity, m / s;
[0109] V S is the longitudinal wave velocity, m / s;
[0110] ρ is the glass density, g / cm 3 .
[0111] In some embodiments, the lower limit of the Young's modulus (E) of the high refractive and high dispersion optical glass of the present invention is 11000×10 7 Pa, the preferred lower limit is 11500×10 7 Pa, and the more preferred lower limit is 12000×10 7 Pa, and the lower limit is preferably 12500×10 7 Pa.
[0112] In some embodiments, the upper limit of the Young's modulus (E) of the high refractive and high dispersion optical glass of the present invention is 15000×10 7 Pa, the upper limit is preferably 14500×10 7 Pa, and the upper limit is more preferably 14000×10 7 Pa, and the upper limit is preferably 13500×10 7 Pa.
[0113] <Bubble Degree>
[0114] The bubble degree of optical glass is tested according to the method specified in GB / T7962.8-2010.
[0115] In some embodiments, the bubble degree of the high refractive and high dispersion optical glass of the present invention is above grade A, preferably grade A. 0 Grade A or above, preferably A 00 class.
[0116] <Abrasion>
[0117] Abrasiveness of optical glass (F A ) refers to the value obtained by multiplying the ratio of the wear volume of the sample to the wear volume (volume) of the standard sample (H-K9 glass) under exactly the same conditions by 100, and is expressed by the following formula:
[0118] F A =V / V 0 ×100=(W / ρ) / (W 0 / ρ 0 )×100
[0119] Where: V—volume wear of the sample being tested;
[0120] V 0 —Volume loss of standard sample;
[0121] W—mass wear loss of the sample being tested;
[0122] W 0 —Abrasion loss of standard sample mass;
[0123] ρ—density of the sample being tested;
[0124] ρ 0 —Standard sample density.
[0125] In some embodiments, the abrasion degree (F A ) has a lower limit of 80, a preferred lower limit of 90, and a more preferred lower limit of 95.
[0126] In some embodiments, the abrasion degree (F A ) has an upper limit of 130, a preferred upper limit of 120, and a more preferred upper limit of 115.
[0127] [Method for producing optical glass]
[0128] The manufacturing method of the high-refractive and high-dispersion optical glass of the present invention is as follows: the glass of the present invention is produced using conventional raw materials and processes, including but not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, etc.), boric acid, etc. as raw materials, and after mixing according to conventional methods, the prepared furnace materials are put into a melting furnace (such as platinum or platinum alloy crucible) at 1200-1450° C. for melting, and after clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.
[0129] [Glass preforms and optical components]
[0130] The glass preform can be made from the high-refractive and high-dispersion optical glass by direct drop molding, grinding, or hot press molding. That is, the molten optical glass can be directly drop molded into a glass precision preform, or the glass preform can be made by mechanical processing such as grinding and grinding, or the preform for molding is made from the optical glass, and then the preform is hot-pressed and then ground to make the glass preform. It should be noted that the means for preparing the glass preform are not limited to the above means.
[0131] As described above, the high-refractive and high-dispersion optical glass of the present invention is useful for various optical elements and optical designs, among which it is particularly preferred to form a preform from the high-refractive and high-dispersion optical glass of the present invention, and use the preform to perform re-hot pressing, precision stamping, etc. to produce optical elements such as lenses and prisms.
[0132] The glass preform and optical element of the present invention are both formed of the high-refractive and high-dispersion optical glass of the present invention. The glass preform of the present invention has the excellent properties of optical glass; the optical element of the present invention has the excellent properties of high-refractive and high-dispersion optical glass, and can provide various optical elements such as lenses and prisms with high optical value.
[0133] Examples of the lens include various lenses having spherical or aspherical lens surfaces, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens.
[0134] [Optical instruments]
[0135] The optical element formed by the high-refractive and high-dispersion optical glass of the present invention can be used to manufacture optical instruments such as photographic equipment, video equipment, projection equipment, display equipment, vehicle-mounted equipment, and monitoring equipment.
[0136] Example
[0137] <High refractive and high dispersion optical glass example>
[0138] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided.
[0139] This embodiment adopts the above optical glass manufacturing method to obtain high refractive and high dispersion optical glasses having the compositions shown in Tables 2 to 4. In addition, the properties of each glass are measured by the test method described in the present invention, and the measurement results are shown in Tables 2 to 4.
[0140] Table 2.
[0141]
[0142]
[0143]
[0144] Table 3.
[0145]
[0146]
[0147] Table 4.
[0148]
[0149]
[0150] <Glass Preform Example>
[0151] The glass obtained from high-refractive and high-dispersion optical glass Examples 1 to 24# is used, for example, by grinding processing, or by molding methods such as re-hot pressing, precision stamping, etc., to make preforms of various lenses, prisms, etc., such as concave meniscus lenses, convex meniscus lenses, double convex lenses, double concave lenses, plano-convex lenses, and plano-concave lenses.
[0152] <Optical Element Embodiment>
[0153] The preforms obtained in the above-mentioned glass preform embodiments are annealed to reduce the internal stress of the glass and fine-tune the refractive index so that the optical properties such as the refractive index reach the desired values.
[0154] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.
[0155] <Optical Instrument Embodiment>
[0156] The optical element obtained by the above-mentioned optical element embodiment is optically designed to form an optical component or optical assembly by using one or more optical elements, and can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips.
Claims
1. High refractive and high dispersion optical glass, characterized in that: Its components, expressed in weight percentage, include: SiO2+B2O3: 10-28%; La2O3+Y2O3+Gd2O3: 46-68%; ZrO2: 1-12%; Nb2O5: 4-20%; TiO2: 4-18%, wherein TiO2 / Y2O3 is 0.3-4.
0.
2. The high-refractive and high-dispersion optical glass according to claim 1, characterized in that: Its components are expressed in weight percentage and further contain: Ta2O5: 0-8%; and / or RO: 0-9%; and / or Rn2O: 0-6%; and / or WO3: 0-6%; and / or ZnO: 0-8%; and / or Al2O3: 0-5%; and / or Yb2O3: 0-10%; and / or GeO2: 0-5%; and / or clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
3. High refractive and high dispersion optical glass, characterized in that: Containing ZrO2, Nb2O5, TiO2, the components are expressed in weight percentage, containing 10-28% SiO2+B2O3 and 46-68% La2O3+Y2O3+Gd2O3, wherein TiO2 / Y2O3 is 0.3-4.0, and the refractive index n of the high-refractive and high-dispersion optical glass is d is 1.92~1.98, Abbe number v d 29~36, wear degree F A The temperature is 80 to 130, and the weather resistance CR is 2 or above.
4. The high-refractive and high-dispersion optical glass according to claim 3, characterized in that: Its components are expressed in weight percentage and contain: ZrO2: 1-12%; and / or Nb2O5: 4-20%; and / or TiO2: 4-18%; and / or Ta2O5: 0-8%; and / or RO: 0-9%; and / or Rn2O: 0-6%; and / or WO3: 0-6%; and / or ZnO: 0-8%; and / or Al2O3: 0-5%; and / or Yb2O3: 0-10%; and / or GeO2: 0-5%; and / or clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
5. The high-refractive and high-dispersion optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage and meet one or more of the following 9 conditions: 1) La2O3 / (TiO2+Nb2O5) is 1.2 to 6.0, preferably La2O3 / (TiO2+Nb2O5) is 1.5 to 5.0, more preferably La2O3 / (TiO2+Nb2O5) is 2.0 to 4.0, and further preferably La2O3 / (TiO2+Nb2O5) is 2.5 to 3.5; 2) TiO2 / Y2O3 is 0.5 to 3.0, preferably TiO2 / Y2O3 is 0.6 to 2.0, and more preferably TiO2 / Y2O3 is 0.75 to 1.5; 3) Y2O3 / B2O3 is 0.4 to 3.0, preferably Y2O3 / B2O3 is 0.5 to 2.5, more preferably Y2O3 / B2O3 is 0.6 to 1.5, and further preferably Y2O3 / B2O3 is 0.7 to 1.2; 4) (B2O3+TiO2) / (SiO2+ZnO) is 1.0 to 10.0, preferably (B2O3+TiO2) / (SiO2+ZnO) is 1.0 to 8.0, more preferably (B2O3+TiO2) / (SiO2+ZnO) is 1.5 to 7.0, and further preferably (B2O3+TiO2) / (SiO2+ZnO) is 2.0 to 5.0; 5) (Ta2O5+Gd2O3) / Y2O3 is less than 1.0, preferably (Ta2O5+Gd2O3) / Y2O3 is less than 0.6, more preferably (Ta2O5+Gd2O3) / Y2O3 is less than 0.4, and further preferably (Ta2O5+Gd2O3) / Y2O3 is less than 0.1; 6) TiO2 / (Nb2O5+WO3) is 0.3 to 3.0, preferably TiO2 / (Nb2O5+WO3) is 0.4 to 2.0, more preferably TiO2 / (Nb2O5+WO3) is 0.6 to 1.5, and further preferably TiO2 / (Nb2O5+WO3) is 0.8 to 1.3; 7) ZnO / (SiO2+B2O3) is 0.5 or less, preferably ZnO / (SiO2+B2O3) is 0.3 or less, more preferably ZnO / (SiO2+B2O3) is 0.2 or less, and further preferably ZnO / (SiO2+B2O3) is 0.1 or less; 8) (Gd2O3+ZnO) / Y2O3 is less than 1.0, preferably (Gd2O3+ZnO) / Y2O3 is less than 0.6, more preferably (Gd2O3+ZnO) / Y2O3 is less than 0.3, and further preferably (Gd2O3+ZnO) / Y2O3 is less than 0.1; 9) WO3 / Y2O3 is less than 0.8, preferably WO3 / Y2O3 is less than 0.6, more preferably WO3 / Y2O3 is 0.02 to 0.5, and further preferably WO3 / Y2O3 is 0.05 to 0.
3.
6. The high-refractive and high-dispersion optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage, wherein: La2O3+Y2O3+Gd2O3: 50-68%, preferably La2O3+Y2O3+Gd2O3: 55-65%; and / or SiO2+B2O3: 10-25%, preferably SiO2+B2O3: 12-20%; and / or ZrO2: 3-10%, preferably ZrO2: 4-9%; and / or Nb2O5: 5-15%, preferably Nb2O5: 7-12%; and / or Ta2O5: 0-4%, preferably Ta2O5: 0-2%, more preferably no Ta2O5; and / or TiO2: 5-13%, preferably TiO2: 6-12%; and / or RO: 0-4%, preferably RO: 0-2%, more preferably no RO; and / or Rn2O: 0-4%, preferably Rn2O: 0-1%, more preferably no Rn2O; and / or WO3: 0-4%, preferably WO3: 0.5-3%; and / or ZnO: 0-4%, more preferably no ZnO, preferably ZnO: 0-2%; and / or Al2O3: 0-3%, preferably Al2O3: 0-1%, more preferably no Al2O3; and / or Yb2O3: 0-5%, preferably Yb2O3: 0-1%, more preferably no Yb2O3; and / or GeO2: 0-3%, preferably GeO2: 0-1%, more preferably no GeO2; and / or clarifier: 0-1%, preferably clarifier: 0-0.5%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.
7. The high-refractive and high-dispersion optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage, among which: SiO2: 1-12%, preferably SiO2: 2-10%, more preferably SiO2: 4-9%; and / or B2O3: 5-18%, preferably B2O3: 6-14%, more preferably B2O3: 7-12%; and / or La2O3: 40-60%, preferably La2O3: 43-58%, more preferably La2O3: 46-53%; and / or Y2O3: 4-20%, preferably Y2O3: 5-15%, more preferably Y2O3: 6-12%; and / or Gd2O3: 0-9%, preferably Gd2O3: 0-5%, more preferably Gd2O3: 0-3%, further preferably Gd2O3: 0-1%.
8. The high-refractive and high-dispersion optical glass according to any one of claims 1 to 4, characterized in that: Its components are expressed in weight percentage, and the total content of SiO2, B2O3, La2O3, Y2O3, ZrO2, Nb2O5 and TiO2 is more than 88%, preferably the total content of SiO2, B2O3, La2O3, Y2O3, ZrO2, Nb2O5 and TiO2 is more than 90%, more preferably the total content of SiO2, B2O3, La2O3, Y2O3, ZrO2, Nb2O5 and TiO2 is more than 92%, and further preferably the total content of SiO2, B2O3, La2O3, Y2O3, ZrO2, Nb2O5 and TiO2 is more than 95%.
9. The high-refractive and high-dispersion optical glass according to any one of claims 1 to 4, characterized in that: The refractive index n of the high-refractive and high-dispersion optical glass is d is 1.92 to 1.98, preferably 1.93 to 1.97, more preferably 1.94 to 1.96, and the Abbe number v d It is 29-36, preferably 30-35, and more preferably 31-34.
10. The high-refractive and high-dispersion optical glass according to any one of claims 1 to 4, characterized in that: The density ρ of the high-refractive and high-dispersion optical glass is 5.10 g / cm 3 Below, preferably 5.00 g / cm 3 Below, more preferably 4.95g / cm 3 Below; and / or thermal expansion coefficient α -30 / 70℃ 85×10 -7 / K or less, preferably 80×10 -7 / K or less, more preferably 75×10 -7 / K or less, more preferably 70×10 -7 / K or less; and / or water resistance stability D W 2 or more, preferably 1; and / or acid resistance stability D A Two or more types, preferably one type; and / or 70 425nm or less, preferably λ 70 420nm or less, preferably λ 70 415nm or less; and / or λ5 is 375nm or less, preferably λ5 is 370nm or less, more preferably λ5 is 365nm or less; and / or weather resistance CR is 2 or more, preferably 1; and / or Knoop hardness H K 650×10 7 Pa or more, preferably 660×10 7 Pa or more, more preferably 670×10 7 Pa or more, more preferably 680×10 7 Pa or more; and / or Young's modulus E is 11000×10 7 Pa~15000×10 7 Pa, preferably 11500×10 7 Pa~14500×10 7 Pa, more preferably 12000×10 7 Pa~14000×10 7 Pa, more preferably 12500×10 7 Pa~13500×10 7 Pa; and / or the bubble degree is A grade or above, preferably A0 grade or above, more preferably A 00 Grade; and / or wear degree F A It is 80-130, preferably 90-120, more preferably 95-115.
11. A glass preform, characterized in that: The optical glass is made of the high-refractive and high-dispersion optical glass described in any one of claims 1 to 10.
12. An optical element, characterized in that The optical glass is made of the high-refractive and high-dispersion optical glass described in any one of claims 1 to 10, or is made of the glass preform described in claim 11.
13. An optical instrument, characterized in that Contains the high-refractive and high-dispersion optical glass according to any one of claims 1 to 10, and / or contains the optical element according to claim 12.
Citation Information
Patent Citations
High-refraction and high- dispersion optical glass and method of manufacture
CN101289276A
Optical glass
CN102674691A
Optical glass with high refraction and high chromatic dispersion, optical element and optical instrument
CN107445474A
Optical glass, glass prefabricated part and optical element
CN111943502A
Optical glass and optical element
JP2014062024A
